FEATURES OF EDDY CURRENT DISTRIBUTION IN A HOLLOW PERFORATED ROTOR OF A POLYFUNCTIONAL ELECTROMECHANICAL CONVERTER - I.N. Kuldyrkaev (National Technical University "Kharkiv Polytechnic Institute", 2013)
Laws of spatial current density distribution in a hollow perforated rotor are obtained in the form of images and dependencies. Behavior of wave resistance subject to rotor slip is identified for a hollow smooth and perforated rotor of various design parameters. An expression for the hollow perforated rotor wave resistance determination is introduced.